2015
DOI: 10.1177/0887403415604899
|View full text |Cite
|
Sign up to set email alerts
|

Out With the Old and in With the New? An Empirical Comparison of Supervised Learning Algorithms to Predict Recidivism

Abstract: Recent research has produced mixed results as to whether newer machine learning algorithms outperform older, more traditional methods such as logistic regression in predicting recidivism. In this study, we compared the performance of 12 supervised learning algorithms to predict recidivism among offenders released from Minnesota prisons. Using multiple predictive validity metrics, we assessed the performance of these algorithms across varying sample sizes, recidivism base rates, and number of predictors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
1
37
0
2
Order By: Relevance
“…As Duwe and Kim (2017) pointed out, and we concur, these results would seem to suggest that the type of statistical methods employed to assess risk for recidivism may depend on the purpose for which risk is being assessed and how they are being used. For example, a large correctional agency looking to automate risk classification within a geographic region or across institutions may require different technologies than an individual assessor who is looking to identify criminogenic needs and generate recommendations for case management.…”
Section: Applications Of Machine Learning (Ml) To Forensic Risk Assessupporting
confidence: 75%
See 1 more Smart Citation
“…As Duwe and Kim (2017) pointed out, and we concur, these results would seem to suggest that the type of statistical methods employed to assess risk for recidivism may depend on the purpose for which risk is being assessed and how they are being used. For example, a large correctional agency looking to automate risk classification within a geographic region or across institutions may require different technologies than an individual assessor who is looking to identify criminogenic needs and generate recommendations for case management.…”
Section: Applications Of Machine Learning (Ml) To Forensic Risk Assessupporting
confidence: 75%
“…Some have suggested that ML may improve the "hit rate" of extant risk-assessment tools (true positives [TPs] plus true negatives [TNs]) such as the LS scales (wormith & Bonta, 2017, p. 135), whereas others have cautioned that the incremental validity of using ML approaches may be "modest," especially when the data are less complex (e.g., a data set containing scores on a single risk-assessment instrument; Garb & wood, 2019Garb & wood, , p. 1464. However, Duwe and Kim (2017) remind us that ML includes many different statistical techniques (e.g., decision tree [DT]-based algorithms, neural networks [NN], and support vector machines [SVMs]) and applications to the criminal justice field are still in their "infancy" (p. 597). Helpful overviews of ML techniques are provided by Tollenaar and van der Heijden (2013) and Duwe and Kim (2017).…”
Section: Applications Of Machine Learning (Ml) To Forensic Risk Assesmentioning
confidence: 99%
“…By applying these transformations, a nonlinear decision boundary is essentially made linear again. This absence of the linearizing transformations when logistic regression is compared to a machine learning model on data having continuous predictors is unfortunately very common in criminological comparison studies, as in [2223, 25, 2829, 35] or restricted to quadratic terms [36]. This absence of linearizing transformations applies to the majority of machine learning comparison studies that include linear statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Berk and Bleich (2013) found that Random Forests had greater accuracy in predicting recidivism than did stochastic gradient boosting, which in turn performed slightly better than did logistic regression. Findings from several studies have concurred that machine learning algorithms offer a significant, albeit more modest, improvement in predictive performance (Breitenbach, Dieterich, Brennan, and Fan, 2009;Duwe and Kim, 2015;Hess and Turner, 2013). Little difference, however, has been found in other research between logistic regression and machine learning algorithms in predicting recidivism (Hamilton, Neuilly, Lee, and Barnoski, 2015;Liu, Yang, Ramsey, Li, and Coid, 2011;Tollenaar and Van der Heijden, 2013).…”
Section: Validitymentioning
confidence: 97%